Investigation into toxin and slime genes in staphylococci isolated from goat milk and goat cheese in southern Turkey - Onen, Sevda Pehlivanlar; Cantekin, Zafer; Mebkhout, Faiza; Aygun, Osman; Ergun, Yasar (Chulalongkorn Univ, 2018)
The aim of this study was to investigate the presence of Staphylococcus aureus and coagulase-negative staphylococci (CNS) isolated from goat milk and cheese, as well as their toxin genes and slime genes. S. aureus and CNS isolates were subjected to polymerase chain reaction (PCR) analyses to determine the prevalence of enterotoxin (sea, seb, sec, sed, see), toxic shock syndrome (TSS) toxin (tst), exfoliative toxin (eta and etb) and slime genes (icaA and icaD). sec, sed and tst genes together were detected in 4 (33.3%), sec + tst genes in 2 (16.7%) and tst gene in 1 (8.3%) of the 12 S. aureus isolates. However, see gene was detected in 6 (9.7%), sed gene and tst gene were detected in 1 (1.6%) and 7 (11.3%) of the 62 CNS isolates, respectively. No sea, seb, see, eta or etb genes were detected in the S. aureus isolates, whereas no sea, seb, sec, eta or etb genes were detected in the CNS isolates. At least one ica gene was present in all S. aureus isolates and in 36 of the 62 CNS isolates. The presence of icaA and icaD genes in the S. aureus isolates was clearly higher than those in the CNS isolates. In conclusion, toxin and slime genes were detected in the S. aureus and CNS isolates from goat milk and goat cheese. The potential risk of enterotoxigenic CNS should not be ignored as well as S. aureus in food safety and public health.
Keywords: Staphylococcus aureus; staphylococci; toxin genes; goat milk; goat cheese